Validation of the robustness of blood-based biomarkers for predicting amyloid-β positivity in Chinese populations - Wang, Ying; Cui, Liang; Pan, Feng-Feng; Zhang, Zhen; Huang, Lin; Miao, Ya; Guan, Yi-Hui; Guo, Qi-Hao (Frontiers in Aging Neuroscience, 2025)
BackgroundBlood-based biomarkers (BBBs) of Alzheimer’s disease (AD) provide a promising, minimally invasive alternative for detecting cerebral amyloid-β (Aβ) pathology. However, a lack of robust validation across diverse platforms and populations has hindered their broader clinical adoption.ObjectiveThis study aimed to cross-platform validation of the robustness of BBBs for predicting Aβ positivity in a Chinese population.MethodsThe whole cohort (N = 1,254) of AD clinical spectrum underwent cognitive assessments, cranial MRI scans, and Aβ PET scans. Subcohort 1 (N = 504) underwent Simoa-based quantification of peripheral blood Aβ40, Aβ42, p-tau181, and NfL. Subcohort 2 (N = 262) underwent additional single molecule assays (Simoa) based quantification of p-tau217 and GFAP. The whole cohorts (Subcohort 1, Subcohort 2, and the remaining population) were measured for the aforementioned six biomarkers (Aβ40, Aβ42, p-tau181, p-tau217, NfL, and GFAP) using light-initiated chemiluminescent assays (LiCA). We validated the robustness of BBBs for predicting Aβ positivity in Chinese populations, with a focus on p-tau217.ResultsThe BBBs of Aβ42/40, p-tau181, p-tau217, GFAP, and NfL have demonstrated remarkable robustness in identifying Aβ positivity within the Chinese population, as evidenced by both LiCA and Simoa assays. Among these markers, p-tau217 has emerged as the most accurate, performing robustness in both the whole cohort and cognitively normal individuals. Utilizing a dual-threshold approach for p-tau217, only 16% of samples fell into the intermediate range, thus requiring additional Aβ PET testing.ConclusionBlood-based biomarkers have demonstrated good robustness for predicting Aβ pathology in the Chinese population, with plasma p-tau217 standing out as the most promising marker for early detection of AD-related changes.